IPE and European Integration: Applying Karl Polanyi's 'the Great Transformation' - Copeland, Paul (2008)
European integration is usually studied within the realms of comparative politics. The multitude of empirical studies concerning the topic have been well suited to its numerous methodologies and analytical frameworks. Comparative politics however, usually ignores the question of why European integration has both progressively deepened and widened during the last thirty years. Therefore there is a distinct absence of how developments in the global political economy determine European integration. Such an approach fails to address the issues of power and constraint within the global economy. We would therefore expect the process to be examined within international political economy, yet there has been a relative neglect of European integration within IPE as it considers the process to be a mere regional response to global developments. This paper argues that European integration is a more complex process than IPE has considered and addresses its relative neglect by applying Polanyiâs 'the Great Transformation'. Firstly, this paper argues that existing comparative politics and IPE approaches to European integration have a number of shortcomings which limits their application. Secondly, to address these limitations this paper applies 'the Great Transformation' to European integration and argues there to be strong parallels between Polanyiâs theory and the process. Thirdly, the paper argues that European integration is much more than a simplistic regional response to globalisation. European integration has been a contradictory process oscillating between neoliberalism and the European Social model. This highlights not just the contradictions of European integration, but also what Polanyi termed the âmarket societyâ. ..PAT.-Unpublished Manuscript
Keywords: European integration; comparative government; globalization; international economic relations; international political economy; neoliberalism

Is Market Liberalization Pathological? Debating the Causes of Corruption in Chinese Banking - Eaton, Sarah (2008)
Neoclassical economists posit that the freeing of market forces will lead, ceteris paribus, to a reduction in levels of corruption. There are several mechanisms through which this hypothesized effect is channeled, the most important of which is competition pressure brought by the entry of foreign firms into the domestic market. The empirical leverage of this approach has been strongly challenged by events of recent years. In China and Russia, market liberalization has not had the expected effects: corruption has exploded alongside market opening. Why? The view among many economists is that the benefits of market opening were stymied by the political logic governing the process of reforms (e.g. cronyism in privatization, trade policy protection of inefficient domestic firms et cetera). The Polanyi-inspired counter-claim is that reform-era corruption is itself an effect of the disembedding of the political economy. My research on corruption in the Chinese banking industry lends empirical insight to the debate. Because the Chinese market is variegated, with some firms being much more exposed to competition than others, there is the opportunity to test these explanatory variables against corruption levels in different segments of the market. On the basis of original fieldwork conducted in China, this paper suggests that the neoclassical economists faith in market opening as an anticorruption mechanism is unwarranted. ..PAT.-Unpublished Manuscript
Keywords: China; banking industry; corruption; disembeddedness; ethics; market liberalization; white collar crimes